Community Empowerment Through Bengkung Application Training for Postpartum Care - Tecky Afifah Santy Amartha; Melyana Nurul Widyawati; Yuniarti; Dhias Widiastuti (Wealth Community Empowerment, 2026)
The postpartum period is a critical phase for maternal health, characterized by physiological recovery and increased risk of complications such as postpartum hemorrhage and musculoskeletal discomfort, including back pain. Traditional abdominal binding practices, such as bengkung, are widely used in Indonesian communities and are believed to support uterine involution, improve abdominal muscle tone, and reduce postpartum discomfort. This community service program aimed to strengthen the capacity of community health cadres through training on the correct and safe application of bengkung as part of postpartum care in Pudakpayung, Semarang. The program employed a community-based training and mentoring approach conducted offline with strict health protocols. Participants consisted of 20 community health cadres who received health education on postpartum physiological changes and hands-on training on bengkung application. Cadres’ skills were assessed using pre-test and post-test evaluations. The results showed that prior to the training, 75% of cadres demonstrated poor skills and 25% demonstrated moderate skills in bengkung application. Following the intervention, 100% of cadres achieved good skill levels. Statistical analysis indicated a significant improvement in cadres’ skills after the training (p < 0.05). The findings suggest that bengkung application training is effective in improving the competencies of community health cadres. This program supports community empowerment and contributes to strengthening community-based postpartum care, with potential benefits for improving maternal comfort and preventing postpartum complications.